OPERATOR PADA RUANG FUNGSI TERINTEGRAL DUNFORD - Solikhin Solikhin; Y.D. Sumanto; Susilo Hariyanto; Abdul Aziz (Diponegoro University, 2018)
An integral Dunford and an operator on Dunford integrable functional space have discussed in this article. The results were shown that the Dunford integrable functional space was a linear function. For every Dunford integrable function on a closed interval, there is an operator that is linear bounded and weak compact operator, whereas its adjoin operator is also linear bounded and weak compact. An operator is weak compact if and only if its adjoin operator is weak compact. Furthermore, the norm of this operator was equal to the norm of its adjoin operator.